Assessing the Influence of Brand Equity Dimensions and Product Quality on Consumer Loyalty: Study of Lifebuoy Soap in DKI Jakarta - Savina Alfi Sahrin; Veronika Santi Paramita (Yayasan Sinergi Kawula Muda, 2026)
This study examines the influence of brand awareness, brand image, and product quality on customer loyalty toward Lifebuoy soap in the DKI Jakarta area, considering the increasingly competitive personal care market that requires companies to build strong and sustainable relationships with consumers. A quantitative research approach was employed by distributing structured questionnaires to 96 respondents who were selected using customized sampling techniques to ensure relevance to the research objectives. The data collected from the respondents were processed and analyzed using multiple linear regression analysis to identify both partial and simultaneous effects of the independent variables on customer loyalty. The findings reveal that brand awareness, brand image, and product quality each have a positive and significant effect on customer loyalty toward Lifebuoy soap, indicating that consumers are more likely to remain loyal when they are familiar with the brand, perceive it positively, and believe that the product delivers consistent quality. Furthermore, the results demonstrate that when these three variables are considered together, they exert a strong combined influence on customer loyalty, highlighting the importance of an integrated branding and quality strategy. Among the variables analyzed, brand image emerged as the most dominant factor affecting customer loyalty, suggesting that consumers’ overall perceptions, associations, and emotional connections with the brand play a crucial role in sustaining long-term loyalty. These findings imply that while brand awareness is important in attracting consumers, it is not sufficient on its own to maintain loyalty unless it is supported by a strong brand image and high product quality. Therefore, companies should prioritize strengthening brand image and maintaining product quality to enhance customer loyalty in the long term.